TLC and UV-Visible Spectrophotometry Validation for Identification of Sildenafil Citrate in Aphrodisiac Herbal Medicine - Azizi, Khodadad Trimawan; Haresmita, Perdana Priya; Permatasari, Desy Ayu Irma (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Traditional medicines, also known as jamu, have sometimes been found to contain medicinal chemicals to enhance the effectiveness of these products. Sildenafil citrate, which is clinically effective in improving erectile function, can cause harmful side effects when included in herbal products. This study, therefore, aims to validate the identification of sildenafil citrate in aphrodisiac herbal medicine using Thin Layer Chromatography (TLC) and UV-visible spectrophotometry. The samples were prepared by macerating 100 mg of the jamu in 96% ethanol for 24 hours. The samples were then evaluated using TLC and a UV-visible spectrophotometer, with validation parameters including linearity, precision, limit of detection (LOD), and limit of quantitation (LOQ). This study uncovered that one of the three samples tested positive for sildenafil citrate, as evidenced by similar Retention factor (Rf) values in two TLC systems. Additionally, analysis using UV-visible spectrophotometry revealed that the average content of sildenafil citrate in the sample was 23.96%, with a relative standard deviation (RSD) of 0.74% and LOD and LOQ values of 10.28 and 34.27 µg/mL, respectively. The methods of analysis, including TLC and UV-visible spectrophotometry, for sildenafil citrate identification are expected to be valuable for regulatory and supervisory agencies in monitoring the distribution of such herbal medicines.